METHOD TO REDUCE POLLUTION AT MAJOR REPAIRS (RECONSTRUCTION) OF URBAN BUILDINGS - M. Yu. Klimenko (Юг России: экология, развитие)
Aim. This article deals with the methods of reducing pollution at major repairs (renovation) of urban buildings. Methods. On the basis of field and theoretical studies we received empirical dependences and characteristic curves of the amounts of: construction waste, total emissions into the atmosphere, the cost of capital repairs (reconstruction) with calculated construction volumes and technical condition of constructions. These graphic and empirical regularities prove the connection of the amount of construction waste and total emissions to the atmosphere with the technical condition of the building during reconstructions. Results. The developed method of reducing environmental pollution during reconstruction of buildings in urban areas includes 5 stages starting from information gathering ending with reusing construction waste. Preliminary forecasting and assessment of major repairs (reconstruction) is possible while making calculations by derived formulas. For planning of measures to reduce pollution we have developed a scheme for treatment of construction wastes and offered alternatives for their use. Conclusions. The use of construction waste, produced during major repairs (renovation) of urban buildings, as secondary raw materials, reduces environmental pollution.